(untitled) (PIONIR: JURNAL PENDIDIKAN, 2023)
Abstract This study aims to analyze how the implementation of character values in children’s education can shape their attitudes and behaviors in the future. Despite the implementation of character education programs through the teaching of Sirah Nabawiyah, there are still some students who have not fully internalized positive character traits. Therefore, the implementation of Sirah Nabawiyah education at SDTQ Nurun Nabi Banda Aceh in the academic year 2022/2023 is expected to be more effective in helping students develop virtuous character. This research will investigate how religious character education values are instilled in children, the factors influencing the implementation of the teaching, and the strategies used by Islamic Education teachers to overcome challenges that arise during the teaching of Sirah Nabawiyah. This is a field research employing a qualitative descriptive approach as the methodology. Data will be collected through interviews, observations, and documentation. The research findings indicate that the implementation of Sirah Nabawiyah education involves various teaching methods centered around the stories from Sirah Nabawiyah, as well as the application of relevant theories and role modeling within the school culture. The role of Islamic Education teachers is crucial in conveying character values to the students. However, the research also reveals several challenges, such as the scarcity of teaching materials that align with the Sirah Nabawiyah curriculum and the low interest in learning among some students. In addressing these challenges, Islamic Education teachers collaborate with the school administration and book publishers to find more comprehensive and suitable teaching resources. Additionally, teachers also diversify their teaching methods to enhance the appeal and interactivity of the learning process for the students. Overall, this research underscores the central role of teachers in shaping the character of students through Sirah Nabawiyah education. By overcoming challenges and adopting innovative teaching strategies, teachers actively contribute to the development of students’ character in line with desired religious values. Keywords: Education, Character, Sirah Nabawiyah Abstrak Penelitian ini bertujuan untuk menganalisis bagaimana penerapan nilai-nilai karakter dalam pembelajaran anak dapat membentuk sikap dan perilaku mereka di masa depan. Meskipun telah dilaksanakan program pembentukan karakter melalui pembelajaran Sirah Nabawiyah, masih ada sebagian peserta didik yang belum sepenuhnya menginternalisasi karakter yang baik. Oleh karena itu, implementasi pembelajaran Sirah Nabawiyah di SDTQ Nurun Nabi Banda Aceh pada Tahun Pelajaran 2022/2023 diharapkan dapat lebih efektif dalam membantu peserta didik membentuk karakter yang berakhlakul karimah. Penelitian ini akan menyelidiki cara nilai-nilai pendidikan karakter religius ditanamkan pada anak, faktor-faktor yang memengaruhi pelaksanaan pembelajaran, serta strategi yang digunakan oleh guru Pendidikan Agama Islam untuk mengatasi kendala yang muncul selama pembelajaran Sirah Nabawiyah. Penelitian ini adalah penelitian lapangan yang menggunakan pendekatan deskriptif kualitatif sebagai metodologi. Data akan dikumpulkan melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa implementasi pembelajaran Sirah Nabawiyah melibatkan berbagai metode pembelajaran yang berpusat pada cerita-cerita dari Sirah Nabawiyah, serta penerapan teori dan keteladanan yang berkaitan dengan budaya sekolah. Peran guru Pendidikan Agama Islam sangatlah penting dalam menyampaikan nilai-nilai karakter kepada peserta didik. Meskipun demikian, penelitian juga mengungkapkan beberapa kendala, seperti keterbatasan bahan ajar yang sesuai dengan materi pembelajaran Sirah Nabawiyah dan minat belajar yang rendah dari sebagian siswa. Dalam menghadapi kendala-kendala tersebut, guru Pendidikan Agama Islam bekerja sama dengan pihak sekolah dan penerbit buku untuk mencari sumber bahan ajar yang lebih lengkap dan sesuai dengan materi. Selain itu, guru juga mengadopsi variasi dalam metode pembelajaran guna meningkatkan daya tarik dan interaktivitas pembelajaran bagi peserta didik. Secara keseluruhan, penelitian ini menegaskan peran sentral para guru dalam membentuk karakter peserta didik melalui pembelajaran Sirah Nabawiyah. Dengan mengatasi kendala dan mengadopsi strategi pembelajaran yang inovatif, para guru berkontribusi secara aktif dalam mengembangkan karakter peserta didik sesuai dengan nilai-nilai religius yang diinginkan. Kata Kunci: Pendidikan, Karakter, Sirah Nabawiyah